1993
DOI: 10.1017/s0952523800003217
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome oxidase in the human visual cortex: Distribution in the developing and the adult brain

Abstract: Cytochrome-oxidase (CO) histochemistry has revealed important functional subdivisions, modules, and processing streams in the macaque visual cortex. The present study is aimed at analyzing the development and characteristics of CO patterns in the human visual cortex by means of histochemistry and immunohistochemistry. At 26 weeks of gestation, both the ventricular and subventricular zones had low levels of CO, while the cortical plate had moderate levels of CO. At birth, supragranular CO-rich zones (puffs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
42
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 53 publications
11
42
0
Order By: Relevance
“…Our results confirm previous reports that the CO staining pattern of humans differs from that of most monkeys (17,(25)(26)(27)(28) and indicate that at least some apes, specifically, chimpanzees and probably also orangutans, possess a humanlike condition. The ape-human pattern is marked by the absence of the thin, dense band of CO staining within layer 4A that is typical of nonhominoids, along with darker staining of layer 4B than is seen in monkeys.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm previous reports that the CO staining pattern of humans differs from that of most monkeys (17,(25)(26)(27)(28) and indicate that at least some apes, specifically, chimpanzees and probably also orangutans, possess a humanlike condition. The ape-human pattern is marked by the absence of the thin, dense band of CO staining within layer 4A that is typical of nonhominoids, along with darker staining of layer 4B than is seen in monkeys.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that the honeycomb is so common in New World and Old World monkeys suggests it should be present in hominoid primates (apes and humans), animals that are closely related to Old World monkeys (24). It is thus surprising that published studies are unanimous in reporting that humans lack a CO-dense 4A band (17,(25)(26)(27)(28). This finding has led WongRiley et al (28) to suggest that the organization of the geniculate projection to layer 4A may have been modified in humans compared with monkeys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3F). Previous studies have shown that the deep portion of the marginal zone also contains abundant synapses (24) and is rich in cytochrome oxidase (19), a metabolic marker of neuronal functional activity (29).…”
Section: Geniculocortical and Cortical Efferent Projectionsmentioning
confidence: 99%
“…Second, there is a rich context of previous studies on the development of visual pathways in animals, including primates (6)(7)(8)(9)(10)(11), providing a basis for comparative analysis. Third, previous studies have described the histological development of the human lateral geniculate nucleus (LGN) (4,(12)(13)(14)(15)(16)(17) and visual cortex (4,11,18,19) in detail. Fourth, the anatomical components of the visual system (i.e.…”
Section: Introductionmentioning
confidence: 99%